Phantom Limb and pain after traumatic lower extremity amputation. - Hnoosh, Adnan H. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Pain after amputation is a common squeal, patients often have a phantom limb sensation too, which can be painful or painless. Objectives: This study describes the sensations and pain reported by patients after traumatic amputation of unilateral lower limb as well as the incidence and epidemiology of those sensations. Patients and methods: A retrospective study of 118 patients who underwent lower limb amputation due to trauma. Patients scheduled for interview by means of a standard questionnaire and examined, days, weeks, months, years, after surgery about limb pain, phantom limb sensations, stump pain, back and shoulder pain . Results: Statistical analysis revealed that the incidence of non-painful sensation was the commonest and more frequent than phantom limb pain. Back pain disturbing the amputee more than phantom limb pain. Phantom pain was significantly less common in patients with below knee amputation than above it. Conclusion: Phantom limb pain and shoulder and back pain problems warranting further clinical attention and analysis.